Injectable Biologics: What Is the Evidence?. (October 2020) - Kubrova, Eva; D'Souza, Ryan S.; Hunt, Christine L.; Wang, Qian; van Wijnen, Andre J.; Qu, Wenchun
Abstract : Abstract: Injectable biologics have attracted considerable interest in the field of musculoskeletal medicine. Biologics encompass a broad and diverse group of human tissue–derived therapeutics. The most commonly reported biologics for use in musculoskeletal conditions include platelet-rich plasma, bone marrow aspirate concentrate, mesenchymal stem cells, microfragmented fat, stromal vascular fraction, amniotic membrane–based products, and autologous conditioned serum. The benefits of biologics in tissue healing and regeneration are thought to be derived from their trophic, paracrine, and immunomodulatory functions. The purpose of this review is to define commonly used injectable biologics and to appraise current evidence on its efficacy in the treatment of musculoskeletal disease.